Up-regulation of MSH2, XRCC1 and ATM genes in patients with type 2 diabetes and coronary artery disease. Issue 3 (September 2015) - Ahmadi, Amirhossein; Behmanesh, Mehrdad; Boroumand, Mohammad Ali; Tavallaei, Mahmoud
Highlights Up-regulation of MSH2, XRCC1 and ATM genes was observed in T2DM patients with CAD. ATM expression was correlated with CAD severity. Single nucleotide polymorphisms in their promoters did not affect mRNA expression. DNA repair genes expression may serve as useful biomarkers.